Issue with Evaluating Costs Over Time in a Context of Medical Guideline Changes: An Example in Myocardial Infarction Care Based on a Longitudinal Study from 1997 to 2018 - Villeneuve T; Trudel X; Gilbert-Ouimet M; Leclerc J; Milot A; Sultan-Taïeb H; Brisson C; Guertin JR (Dove Medical Press, 2022)
Tania Villeneuve,1 Xavier Trudel,1,2 Mahée Gilbert-Ouimet,2,3 Jacinthe Leclerc,4,5 Alain Milot,6 Hélène Sultan-Taïeb,7,8 Chantal Brisson,1,2 Jason Robert Guertin1,2 1Université Laval, Département de médecine sociale et préventive, Quebec City, Canada; 2Centre de recherche du Centre hospitalier universitaire de l'Université Laval, Quebec City, Canada; 3Université du Québec à Rimouski, Département des sciences de la santé, module des sciences infirmières, Lévis, Canada; 4Université du Québec à Trois-Rivières, Département des sciences infirmières, Trois-Rivières, Canada; 5Centre de recherche de l'Institut universitaire de cardiologie et de pneumologie de Québec-Université Laval, Quebec City, Canada; 6Université Laval, Département de médecine, Quebec City, Canada; 7Université du Québec à Montréal (UQAM), School of Management, Montreal, Canada; 8CINBIOSE, Montreal, CanadaCorrespondence: Jason Robert GuertinCentre de recherche du CHU de Québec - Université Laval, Axe Santé des Populations et Pratiques Optimales en Santé, Hôpital du Saint-Sacrement, 1050 Chemin Ste-Foy, local J1-09B, Québec City, Québec, G1S 4L8, CanadaTel +1 418-682-7511, poste 82516Email jason.guertin@fmed.ulaval.caBackground: Cost studies appear sporadically in the scientific literature and are rarely revised unless drastic technological advancements occur. However, health technologies and medical guidelines evolve over time. It is unclear if these changes render obsolete prior estimates. We examined this issue in a cost study in the context of patients' first myocardial infarction (MI), a clinical area prone to such continuous evolution in care.Methods: We conducted a longitudinal cost analysis based on a Quebec cohort. Quebec health administrative databases were used to identify incident MI cases using diagnostic codes from the international classification of diseases (ICD-9 and ICD-10). Physician fees and hospitalization costs (ie, costs incurred by the hospital center) were derived from administrative databases and a university hospital's finance department. All costs were converted to 2019 Canadian dollars. Nonparametric bootstraps were used to estimate 95% confidence intervals (CI) of the average costs of an episode of care. Generalized linear regressions were used to examine temporal trends of cost.Results: Our study sample consists of 261 patients hospitalized for a first MI. The average total cost for this first event was estimated at $5782 (95% CI: $5293 - $6373). Though total costs remained stable over time, physician fees increased by 123% ($1240 vs $2761) whereas total hospital length of stay dropped by 17% (6.6 vs 5.5 days) over the 21-year period.Conclusion: Patients' first MI hospitalization impose an economic burden on the healthcare system. Though overall costs remained stable, our results suggest that some cost components varied over time.Keywords: cost study, methods, observational data, myocardial infarction, longitudinal study